Feeding behaviour of Aphids craccivora (Koch) on cowpea cultivars with different levels of aphid resistance - Mesfin, T.; Thottappilly, G.; Singh, S.R. (Wiley, 1992)
The feeding activity of Aphis craccivora (Koch) was monitored on cowpea plants of aphid‐susceptible (Vita 7) and aphid‐resistant (TVu 801) cultivars, using an AC electronic feeding monitoring system. Waveforms corresponding to salivation, phloem ingestion and non‐phloem ingestion were observed. Aphids probing on the resistant cultivar showed a significantly reduced ingestion of phloem sap compared with those aphids which fed on the susceptible cultivar. The insect also made more brief and repeated probes on TVu 801. In addition, the duration of non‐probing activities and non‐phloem ingestion was shorter on the susceptible than on the resistant cultivar.